Implementasi K-13 dalam Meningkatkan Prestasi Belajar Siswa di MA Putri Satu Pragaan Al-Amien Prenduan - Muhammad Nurul Yaqin; Anggiwidiyati Anggiwidiyati (Jurnal Kajian Ilmu Pendidikan, Bahasa dan Komunikasi, 2026)
Curriculum and education is an inseparable relationship because the curriculum is very important in education, if there is no curriculum then education will not be realized because the curriculum is a guideline for the maintenance of education in addition to that the curriculum is always adapted to the existing situation and circumstances. One of the educational institutions that are active in applying K-13 is MA Putri 1 Al-Amien Prenduan, where this institution is under the umbrella of Al-Amien Prenduan Pesantren Pondok. Pondok Pesantren Al-Amien Prenduan is composed of 4 parent institutions, namely Tarbiyatul Banaat Diniyah Al-Amien (TIBDA), Madrasah Tsanawiyah Al-Amien (MTsA) accredited status in 2005, Madrasah Aliyah Al-Amien (MAA) accredited status in 2004, Madrasah Aliyah Skills (MAK), and the Middle School of Information Technology (SMK IT) established in 2008. This study uses a qualitative-descriptive approach. As for the data collection technique in this research, it is using methods of interview, observation and documentation. The interview method used is a structured interview to extract detailed data from the source. From the findings in the field obtained based on the results of interviews, documentation, and observations can be concluded into several points: 1) the K13 learning plan in improving student performance performed by the teacher is by first mapping the KD by establishing the theme that is in the teacher's book. 2) K13 learning process in improving student learning performance more emphasizes cognitive aspects with emotional, and psychomotor support. 3) Authentically evaluate in K13 learning to improve this student’s learning performance using various techniques and starting instruments